The Sclerophyllous Eucalyptus camaldulensis and Herbaceous Nicotiana tabacum Have Different Mechanisms to Maintain High Rates of Photosynthesis - Huang, Wei; Tong, You-Gui; Yu, Guo-Yun; Yang, Wei-Xian (Frontiers in Plant Science, 2016)
It is believed that high levels of mesophyll conductance (gm) largely contribute to the high rates of photosynthesis in herbaceous C3 plants. However, some sclerophyllous C3 plants that display low levels of gm have high rates of photosynthesis, and the underlying mechanisms responsible for high photosynthetic rates in sclerophyllous C3 plants are unclear. In the present study, we examined photosynthetic characteristics in two high-photosynthesis plants (the sclerophyllous Eucalyptus camaldulensis and the herbaceous Nicotiana tabacum) using measurements of gas exchange and chlorophyll fluorescence. Under saturating light intensities, both species had similar rates of CO2 assimilation at 400 μmol mol-1 CO2 (A400). However, E. camaldulensis exhibited significantly lower gm and chloroplast CO2 concentration (Cc) than N. tabacum. A quantitative analysis revealed that, in E. camaldulensis, the gm limitation was the most constraining factor for photosynthesis. By comparison, in N. tabacum, the biochemical limitation was the strongest, followed by gm and gs limitations. In conjunction with a lower Cc, E. camaldulensis up-regulated the capacities of photorespiratory pathway and alternative electron flow. Furthermore, the rate of alternative electron flow was positively correlated with the rates of photorespiration and ATP supply from other flexible mechanisms, suggesting the important roles of photorespiratory pathway and alternative electron flow in sustaining high rate of photosynthesis in E. camaldulensis. These results highlight the different mechanisms used to maintain high rates of photosynthesis in the sclerophyllous E. camaldulensis and the herbaceous N. tabacum.